Pasraman Sebagai Upaya Peningkatan Mutu Pendidikan Berbasis Budaya Dan Spiritual - Ni Putu Winanti (Jayapangus Press, 2021)
Pasraman, ashram, padukuhan or gurukula are traditional education systems in Hinduism that have been rooted since ancient times. Hindu that realizes that education is an important aspect in human life. In Bali, the history of Pasraman has been known since ancient times. In folk tales there are scattered touches of education and the existence of padukuhan or pasraman creating a place for Bali to receive education in ancient times. This article describes Pasraman as an effort to improve the quality of education based on spiritual and culture. The research was conducted at pasraman in Bali with qualitative descriptive and data analysis using Ethnographic Content Analysis (ECA). The results showed that Pasraman still find the spirit and its relevance in today's modern era. Because the character order becomes an important foundation to support efforts to improve the quality of national education. It will also directly linked to efforts to improve human resources Excelling as proclaimed by the provincial government of Bali.